Ingestible devices for long-term gastrointestinal residency: a review. (4th August 2021) - Mau, Musharrat Mustaree; Sarker, Sunandita; Terry, Benjamin S
Abstract: Ingestible devices have been gaining attention from the medical community due to their noninvasive use in diagnostics and treatment of the gastrointestinal (GI) tract. However, their passive locomotion limits their GI residency period. Ingestible sensors residing in the GI tract are capable of providing continuous data, while long-acting ingestible drug delivery systems can reduce medication nonadherence. This paper presents a comprehensive overview of the state-of-the-art, long-term ingestible devices (LTIDs). Additionally, this review summarizes the current status of ingestible devices that persist in the GI tract for a prolonged period, as well as their inhabitance mechanisms and applications. Also included are relevant information about the GI structure and design considerations for understanding the significance and challenges associated with LTIDs. Finally, we discuss several potential applications of the LTIDs for therapeutic intervention in the GI tract and monitoring the physiology and pathophysiology of the GI tract for an extended period.